Edaphic and temporal patterns of Tuber melanosporum fruitbody traits and effect of localised peat-based amendment - Garcia-Barreda, Sergi; Marco, Pedro; Martín-Santafé, María; Tejedor-Calvo, Eva; Sánchez, Sergio (Scientific reports, 2020)
In Tuber melanosporum cultivation, fruitbody traits are gaining relevance due to their increasing prominence on prices. We investigated the edaphic and temporal patterns of fruitbody traits and characterised the effect of truffle nests (localised peat-based amendment supplemented with T. melanosporum spores) on traits. We monitored fruitbody traits throughout two fruiting seasons in three blocks along a soil gradient. Each trait followed specific edaphic and temporal patterns. The number of fruitbodies per dig and spore maturity followed characteristic within-season trends, whereas fruitbody weight and infestation by truffle beetles were subject to complex interactions among edaphic and temporal variables, suggesting a relevant influence of annual environmental conditions. The application of truffle nests increased fruitbody depth, improved its shape and decreased infestation by truffle beetles. Nests increased the number of fruitbodies per dig, but only in two of the soils, suggesting a relevant role of the bulk soil/substrate interface in fruiting initiation. These results outline a complex scenario, with each trait being differently affected by environmental factors. In this scenario, nests proved to effectively modify several traits, although not always in the desired direction.